2012
DOI: 10.1103/physreva.85.060102
|View full text |Cite
|
Sign up to set email alerts
|

Using technical noise to increase the signal-to-noise ratio of measurements via imaginary weak values

Abstract: The advantages of weak measurements, and especially measurements of imaginary weak values, for precision enhancement, are discussed. A situation is considered in which the initial state of the measurement device varies randomly on each run, and is shown to be in fact beneficial when imaginary weak values are used. The result is supported by numerical calculation and also provides an explanation for the reduction of technical noise in some recent experimental results. A connection to quantum metrology formalism… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 24 publications
2
107
1
Order By: Relevance
“…An important step was made in this question when Feizpour, Xingxing, and Steinberg [10] were able to consider a more general kind of technical noise and show that so long as it has a long correlation time, WVA also helps suppress it in the signal-to-noise ratio (SNR). In other closely related work, Kedem [17], Brunner and Simon [18], and Nishizawa et al [19] also showed an increased performance of the SNR in the presence of technical noise.…”
Section: Introductionmentioning
confidence: 75%
“…An important step was made in this question when Feizpour, Xingxing, and Steinberg [10] were able to consider a more general kind of technical noise and show that so long as it has a long correlation time, WVA also helps suppress it in the signal-to-noise ratio (SNR). In other closely related work, Kedem [17], Brunner and Simon [18], and Nishizawa et al [19] also showed an increased performance of the SNR in the presence of technical noise.…”
Section: Introductionmentioning
confidence: 75%
“…An informationtheoretical advantage has been conjectured several times [15,19,28,39]: and a recent study by Harris, Boyd and Lundeen [25] gives these conjectures a theoretical underpinning. We refer the reader to [25] for a full analysis, but the rough argument is as follows: for a deterministic strategy, there will be some maximum photon flux for 2 )r , vertical grey bars) shown as a guide for the eye.…”
Section: Saturationmentioning
confidence: 99%
“…Since weak values may channel information into the s θ variable (with θ not necessarily zero, which is impossible in standard measurements), this can be useful in the case where a more stable measurement of s θ (than of x) is available [28]. See Fig.…”
Section: Transverse Jittermentioning
confidence: 99%
See 1 more Smart Citation
“…protocols with di erent physics, there may be scope for altering the apparatus in a fashion which tailors it to better t the available hardware. In a time-domain experiment, for example, a frequency analyser is sometimes preferred to a stopwatch [10,13]. However, unless there is a severe mismatch between the quality of detection in the two variables, imaginary weak values will not provide a signi cant advantage [12].…”
Section: Imaginary Weak Valuesmentioning
confidence: 99%